A comparative study of the land required for food and cooking fuel in rural India. (November 2019) - Das, Karabee; Nonhebel, Sanderine
Abstract: Land is a limited resource that provides food and cooking fuel to the rural population. In this paper, we determine the land required for food production and compare it with the land required for cooking fuel (i.e. fuelwood) for six different regions of India. We use regional data to assess the land requirements for both food and fuelwood. Dietary patterns and agricultural yields are the major drivers of land demand for food production. The average land requirement for food is about 1000 m 2 /cap/yr, but the values range between 800-1300 m 2 /cap/yr. The greatest proportion of this land requirement is for cereals, especially rice and wheat. Determining the land needed for cooking fuel requires biomass productivity and fuelwood use. We found that the average land requirement for fuelwood is about 3 to 7 times larger than the area required to produce food. Thus, there is a wide disparity in land demand between all the regions of India. Dietary change is not an option as rural inhabitants are already consuming less than their urban counterparts. Changes to cooking fuels could be another option. This comparative study shows the high demand for land for cooking fuel in comparison to food. It implies that, from a land requirement perspective, reducing the fuelwood consumption and shifting to a more efficient cooking fuel would be a better option. Highlights: Land required for food and fuelwood in rural India was studied. Large regional variations in food consumption and cooking fuel use were found. Land requirement for food is about 1000 m 2 /cap/yr. Land required for fuelwood was seven times as higher than land required for food. This study is typical for rural areas in developing nations comprising three billion people.